Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1432-1033.1993.tb18032.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the resistance to heat and hydrogen peroxide stresses in COS cells transiently expressing wild type or deletion mutants of the Drosophila 27‐kDa heat‐shock protein

Abstract: The Drosophila melanogaster small heat‐shock protein, hsp27 (Dhsp27) belongs to a family of polypeptides which shares a sequence related to α‐crystallin and which protect cell against heat shock. Dhsp27 accumulates following heat shock and, in absence of stress, in the central nervous system, imaginal discs and the gonads of the developing fly. Two internal and adjacent deletion mutants in the conserved α‐crystallin domain of Dhsp27 were constructed. Expression vectors containing either the coding sequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(84 citation statements)
references
References 56 publications
3
79
0
2
Order By: Relevance
“…For example, involvement of HSP70 in protection of ischemic brain was suggested [11], whereas transient ischemia can result in apoptotic death of neurons [28]. Both HSP70 and HSP27 were found to be protective against necrosis caused by H20 2 and TNF [29,30]. At the same time, it was shown that low doses of oxidants are able to bring about apoptotic death [4,31], therefore, it is very probable that HSPs may perform an important protective function against oxidant-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, involvement of HSP70 in protection of ischemic brain was suggested [11], whereas transient ischemia can result in apoptotic death of neurons [28]. Both HSP70 and HSP27 were found to be protective against necrosis caused by H20 2 and TNF [29,30]. At the same time, it was shown that low doses of oxidants are able to bring about apoptotic death [4,31], therefore, it is very probable that HSPs may perform an important protective function against oxidant-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, for detection of Hsp27 dimers, cells were lysed in nonreducing SDS buffer without dithioerythritol. Cell lysates were then subjected to SDS-polyacrylamide gel electrophoresis (Laemmli, 1970), and immunoblots were performed as previously described (Mehlen et al, 1993). The detection of immunoblots was performed with the ECL system (Amersham Corp.).…”
Section: Gel Electrophoresis and Immunoblottingmentioning
confidence: 99%
“…The small HSP family (sHSP) exhibit a monomeric molecular mass ranging between 9 and 42 kDa (Arrigo and Landry, 1994). Their overexpression enhances the survival of mammalian cells exposed to a variety of death stimuli including heat (Landry et al, 1989), oxidative stress (Hout et al, 1991;Mehlen et al, 1993), anticancer drugs (Hout et al, 1991;Garrido et al, 1996Garrido et al, , 1997, TNF-a (Mehlen et al, 1995a), anti-Fas agonistic antibodies and staurosporine (Mehlen et al, 1996a). The biochemical mechanisms proposed to account for the sHSP protective e ect include molecular chaperoning of non-native proteins (Jakob et al, 1993) or capping/decapping enzymes (Lavoie et al, 1993(Lavoie et al, , 1995, modulation of the cellular detoxifying machinery to cope with oxidative stress (Mehlen et al, 1996b) and interaction with the cytochrome c-mediated pathway of apoptosis by preventing caspase-9 activation (Garrido et al, 1999).…”
mentioning
confidence: 99%